A new genus for North American Cicadetta species (Hemiptera: Cicadidae) - Marshall, David C.; Hill, Kathy B. R. (Zootaxa, 2017)
The generic classification of cicadas within the globally distributed tribe Cicadettini (Hemiptera: Cicadidae) has been challenging due to their often conservative morphology. A recent molecular analysis has indicated that the six North American taxa currently classified in Cicadetta are unrelated to the European type species of Cicadetta, C. montana Scopoli. Here we identify a set of diagnostic morphological characters for a new genus, which we distinguish from its closest relatives in Eurasia and Australasia.